Short-Term Attentional Perseveration Associated with Real-Life Creative Achievement - Zabelina, Darya; Beeman, Mark (Frontiers in Psychology, 2013)
There are at least two competing hypotheses of how attention interacts with creative cognition, although they are not mutually exclusive. The first hypothesis is that highly creative people are particularly flexible at switching their attention – that is, they adaptively shift focus among different attentional levels using cognitive control. The second, less common, view is that creative people exhibit attentional persistence, or an ability for sustained attention. We suggest these two views need not be competing, as they may both operate, but on different time scales or on different components of creativity. In the present study we examined the role of attention in real-world creative achievement and in divergent thinking. In Experiment 1 participants with high and low real-world creative achievements identified whether the stimulus contained letters S or H within hierarchically constructed letters (e.g., large S made of small Es – global level; large E made up of small Ss – local level), which were presented in blocks of 8 trials per level. In Experiment 2 participants with high, medium, and low creative achievements identified the same stimulus letters, but in blocks of 5, 7, and 9 trials per level. Results from both studies indicated that people with high creative achievements made significantly more errors on trials in which they had to switch the level of attention, even after controlling for general intelligence. In Experiment 2, divergent thinking was also assessed, but it was not related to switching cost. Results from both experiments demonstrate that real-world creative acts relate to increased levels of attentional persistence, even if it comes with the cost of perseveration in certain circumstances.